The generalized SIC-OEP formalism and the generalized SIC-Slater approximation (stationary and time-dependent cases) - Messud, J.; Dinh, P. M.; Reinhard, Paul-Gerhard; Suraud, E. (Annalen Der Physik, 2011)
present a generalized formulation of the Optimized Effective Potential (OEP) approach to the Self Interaction Correction (SIC) problem in Time Dependent (TD) Density Functional Theory (DFT). The formulation relies on the introduction of a double set of single electron orbitals. It allows the derivation of a generalized Slater approximation to the full OEP formulation, which extends the domain of validity of the standard Slater approximation. We discuss both formal aspects and practical applications of the new formalism and give illustrations in cluster and molecules. The new formalism provides a valuable ansatz to more elaborate (and computationally very demanding) full TD OEP and full TD SIC calculations especially in the linear domain. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-07-24
Keywords: irradiation.; self-interaction correction; Time Dependent Density Functional Theory